The regulation of tax practitioners in South Africa: a proposed model - Woodbridge, Taryn (Rhodes University, Faculty of Commerce, Department of Accounting, 2006)
Tax practitioners in South Africa have been operating in an unregulated tax industry. This has allowed certain tax practitioners to fail in their duties to their clients, as many do not have to abide by any code of conduct or ethical principles, to the detriment of the public. Other than the provisions in the Income Tax Act, 58 of 1962, there has been no regulation. As a result of losses suffered by taxpayers either through the incompetence, ignorance or negligence of a tax practitioner, as substantiated by case law, and increased costs borne by the South African Revenue Services due to unnecessary queries and tax disputes, the Minister of Finance, Trevor Manuel, introduced the concept of tax industry regulation in his Budget Speech in 2002. This resulted in the introduction of section 67 A into the Income Tax Act, providing for a registration process for tax practitioners. All practising tax practitioners were required to register with the Commissioner for the South African Revenue Services by 30 June 2005. In addition, a discussion paper was issued in 2002 setting out the proposal of the Revenue Services to regulate the tax industry through the formation of an Association of Tax Practitioners. This proposal includes various contentious issues and casts significant doubt on whether the proposed model is the most suitable. The goal of the research was therefore to evaluate the current status of tax advisory services in order to demonstrate the need for regulation and to compare the proposed SARS model with two established regulatory authorities: the Estate Agency Affairs Board and the Australian Tax Agents Board. A conceptual model for regulation was developed in order to test all the models against a simple regulatory framework to determine whether each was aligned to certain best practices proposed in this framework. The research methodology was qualitative in nature, involving the critical interpretation of documentary data and data generated during a public discussion forum of tax practitioners. It was concluded that the SARS proposal is too prescriptive and, at the same time, too broad in its scope. In order to address the key objective, identified as protection of the taxpaying public, a simplified regulation procedure was recommended, which would adhere to the proposed regulatory framework.,KMBT_363
Keywords: Income tax -- Law and legislation -- South Africa; Taxation -- Law and legislation -- South Africa; South African Revenue Service